Euthanasia and the right to life: ethical-social problems - Tarantino, Antonio (Medicina e Morale, 1992)
The problem of euthanasia today is no longer characterized by its eugenetic nature, but is now based on the ideological movement of secularization, in which the rights of the patient include the protection from his disease. Therefore what is really important is the quality of life and not life itself. The author accepts this statement, but he cannot accept the absurd conclusion of the refusal of life in order to avoid suffering and pain, because these are a substantial part of human existence. He concludes that only disagreeing with euthanasia does one completely respect the essential rights of all human beings.